Knowledge and Attitude of Mothers Regarding Early Childhood Health Protocol Implementation During the Covid-19 Pandemic - Roselina Tambunan; Monika Ginting (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: Since Sars-CoV-2, a new strain of the coronavirus, has become a global pandemic, we need to take precautionary measures and establish health procedures. The study aimed to determine the relationship between knowledge and mothers' attitudes regarding the application of health protocols for early childhood during the Covid-19 pandemic at Majalengka Regency. Method: This cross-sectional study was conducted in 2021 with a sample size of 51 mother-and-child pairs from kindergartens in the Majalengka Regency of West Java. Knowledge and attitude measurement using good validity and reliability reported questionnaires. Result: The results of the mother's knowledge were good, namely 82.4%, while the level of knowledge was sufficient at 17.6%. The results of the mother's attitude supported 56.9% and did not support 43.1%. The cross-tabulation results obtained a p-value of 0.714, which is greater than 0.05, meaning there is no relationship between knowledge and mothers' attitudes about the application of health protocols in early childhood. Conclusion: Based on the study result, family members and nurses in public health centers can increase counseling regarding health protocols for early childhood mothers. They need to work with health workers or local health agencies to counsel and motivate mothers to increase attitudes toward implementing health protocols in early childhood during the Covid-19 pandemic.